Sports turf & amenity grasses : a manual for use and identification - Aldous, David, 1946- (Land Links, 2002)
Sports Turf and Amenity Grasses is a comprehensive reference for anyone involved with the selection and maintenance of grasses used in sports and amenity areas in all areas.